2010
DOI: 10.1002/jcb.22520
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin‐induced cell migration and COX‐2 production mediated by the bradykinin B1 receptor in glioma cells

Abstract: Bradykinin is produced and acts at the site of injury and inflammation. Recent reports have also shown that bradykinin selectively modulates blood-tumor barrier permeability. However, the molecular mechanisms and pathologic roles underlying bradykinin-induced glioma migration remain unclear. Glioma is the most common primary adult brain tumor, with a poor prognosis because of the ease with which tumor cells spread to other regions of the brain. In this study, we found that bradykinin increases the cell migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 49 publications
5
43
0
1
Order By: Relevance
“…1-3). This is in accordance with recent results published by Lu et al (27), demonstrating that two human GBM cell lines U-138-MG and U-251-MG express functional B1R and B2R. They showed that proliferative effects were induced by incubation with DBK and BK.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…1-3). This is in accordance with recent results published by Lu et al (27), demonstrating that two human GBM cell lines U-138-MG and U-251-MG express functional B1R and B2R. They showed that proliferative effects were induced by incubation with DBK and BK.…”
Section: Discussionsupporting
confidence: 93%
“…In vivo studies on kinin B1 (B1R) and B2 receptors (B2R) revealed that B2R was increasingly expressed with augmenting malignancy of glioma (16) and GBM cells (26). Reportedly, B1R was not relevant for GBM cell invasion (15); however, B1R expression upregulation in GBM cells was confirmed by Lu et al (27). In GBM tissue, B1R expression may be induced by high levels of inflammatory cytokines produced by tumor infiltrating immune cells (28).…”
Section: Discussionmentioning
confidence: 93%
“…Recently, Ang-II exhibited in vitro and in vivo the potential to enhance the expression of AR in prostate cancer cells through angiotensin II type-1 receptor (AT1R) [106] . In addition, Ang-II and BK receptors have been implicated in the development, growth, angiogenesis and metastasis in a wide number of tumors [101,102,[107][108][109][110][111] . For instance, Ang-II and BK stimulated DNA synthesis in pancreatic cancer cells [112] .…”
Section: Gpcrs Activated By Hormonesmentioning
confidence: 99%
“…For instance, Ang-II and BK stimulated DNA synthesis in pancreatic cancer cells [112] . In the context of this malignancy, a cross-talk between insulin/ insulin like growth factor-I (IGF-1) receptors and Ang-II and BK-activated GPCRs has been reported [111][112][113][114] . In particular, insulin induced the potentiation of Ang-II and BK-dependent signaling through the PI3K/Akt/mTOR transduction pathway [113] .…”
Section: Gpcrs Activated By Hormonesmentioning
confidence: 99%
“…Outros estudos utilizando modelo de isquemia e reperfusão cerebral em ratos ou camundongos nocautes para os receptores de bradicinina mostraram que o B1R contribui para a lesão cerebral enquanto o B2R é benéfico [85,86]. Este efeito deletério de B1R também foi demonstrado em um modelo de colite e tumor cerebral [87,88].…”
Section: Lesão De Isquemia E Reperfusão Renalunclassified